Thermal Comfort Challenges in Construction: Evaluating the Role of Clothing Insulation and Physiological Responses - Budiawan, Wiwik; Limbong, Vanri Apri Yanto; Prastawa, Heru; Saputra, Dhimas Wachid Nur (Universitas Ahmad Dahlan, 2025)
Construction workers are frequently exposed to extreme outdoor temperatures, which impact their thermal comfort and physiological well-being. High air temperatures and inappropriate clothing insulation can lead to heat stress, reducing worker productivity and increasing health risks. This study aims to evaluate the relationship between clothing insulation, environmental conditions, and physiological responses to improve thermal comfort for construction workers. It contributes to the field by providing empirical data on how clothing insulation influences thermal comfort and physiological responses in a hot and humid construction environment. The findings highlight critical insights for ergonomic work wear design to mitigate heat stress. Data collected over four weeks at an active construction site. Environmental parameters, including air temperature, humidity, air velocity, and solar radiation, were measured using a weather station. Physiological responses, such as heart rate, core body temperature, and skin temperature, were monitored using wearable sensors. Subjective thermal comfort was assessed through structured questionnaires. Association between air temperature, clothing insulation, and skin temperature (p < 0.05). The average air temperature exceeded ASHRAE’s comfort range, and workers experienced increased physiological strain due to high clothing insulation values. Most workers reported discomfort, with 75% indicating that the thermal environment was unacceptable. The study also confirmed that ergonomic clothing adjustments, such as lightweight, breathable fabrics and cooling vests, could enhance thermal comfort and reduce heat stress. These findings emphasize the importance of optimizing work wear to improve construction workers' well-being. Future research should explore innovative materials and cooling technologies to enhance thermal regulation in extreme working environments.